2020
DOI: 10.1097/qai.0000000000002417
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and Cytomegalovirus Associate With Atherosclerosis Among HIV Patients After 5 Years on ART

Abstract: Objectives: Atherosclerosis has been linked with periodontitis in the general population and with persistent immune activation and a high burden of cytomegalovirus (CMV) in HIV patients responding to antiretroviral therapy (ART). Here, we assess risk factors for cardiovascular changes in younger HIV patients representative of patient populations in Asia. Study Design: HIV-infected adults (n = 82) with <200 CD4 T-cells/μl were examined as they began A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…JakCCANDO was a comprehensive survey of clinical and immunological responses in 75 HIV-infected patients who began ART with < 200 CD4 T-cells/µl in the HIV outpatient clinic of a tertiary hospital (Cipto Mangunkusumo Hospital, Jakarta, Indonesia) [ 5 , 6 , 11 ]. Here we describe a subset of 32 patients who attended a 5-year follow up ( V isit 60 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…JakCCANDO was a comprehensive survey of clinical and immunological responses in 75 HIV-infected patients who began ART with < 200 CD4 T-cells/µl in the HIV outpatient clinic of a tertiary hospital (Cipto Mangunkusumo Hospital, Jakarta, Indonesia) [ 5 , 6 , 11 ]. Here we describe a subset of 32 patients who attended a 5-year follow up ( V isit 60 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hsue et al [ 9 ] reported correlations between T-cell responses to CMV and increased cIMT in HIV patients in the US, and Knudsen et al [ 10 ] described a direct association between levels of CMV-reactive antibodies and cIMT in Danish patients stable on ART. In our cohort, periodontitis and levels of CMV antibodies were independent predictors of raised cIMT after 5 years on ART [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The connection between periodontitis, viruses, and atherosclerosis was also sought among HIV patients 137 . HIV‐infected adults (n = 82) were examined as they began antiretroviral therapy and after 3 months.…”
Section: The Perio‐systemic Connection: Connected By Viruses or By Ba...mentioning
confidence: 99%
“…The connection between periodontitis, viruses, and atherosclerosis was also sought among HIV patients. 137 HIV-infected adults (n = 82) were examined as they began antiretroviral therapy and after 3 months. Further, 32 patients were reassessed after 5 years, alongside 32 age-matched healthy controls.…”
Section: Atherosclerosisvirusesandperiodontitis Associationmentioning
confidence: 99%